2008
DOI: 10.1016/j.jsbmb.2008.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Ligand specificity and evolution of liver X receptors

Abstract: Liver X receptors (LXRs) are key regulators of lipid and cholesterol metabolism in mammals. Little is known, however, about the function and evolution of LXRs in non-mammalian species. The present study reports the cloning of LXRs from African clawed frog (Xenopus laevis), Western clawed frog (Xenopus tropicalis), and zebrafish (Danio rerio), and their functional characterization and comparison with human and mouse LXRs. Additionally, an ortholog of LXR in the chordate invertebrate Ciona intestinalis was clone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
48
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(49 citation statements)
references
References 43 publications
1
48
0
Order By: Relevance
“…2C). This bile profile is quite similar to our prior analysis of biliary bile from Silurana tropicalis (Western clawed frog, also known as Xenopus tropicalis), a related frog species (40). GC-MS analysis (data not shown) showed that most of the bile salts from African clawed frog were in the 5b (A/B cis) orientation, with only a minor fraction (,10%) in the 5a orientation.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…2C). This bile profile is quite similar to our prior analysis of biliary bile from Silurana tropicalis (Western clawed frog, also known as Xenopus tropicalis), a related frog species (40). GC-MS analysis (data not shown) showed that most of the bile salts from African clawed frog were in the 5b (A/B cis) orientation, with only a minor fraction (,10%) in the 5a orientation.…”
Section: Resultssupporting
confidence: 83%
“…It is also worth noting that the variability of FXRs across vertebrate species contrasts markedly with the liver X receptors, closely related NHRs whose endogenous ligands are oxysterols (4). Liver X receptors a and b (NR1H3 and NR1H2, respectively) are much more highly conserved in sequence and pharmacology across vertebrates than FXRs (30,40).…”
Section: Discussionmentioning
confidence: 99%
“…Amphibian species have some of the most complex biliary bile salt profi les found within vertebrates, with some species having signifi cant amounts of C 27, C 26 , C 28 , or other side chain length bile alcohols as well as C 27 bile acids and C 24 bile acids ( 9,22,(72)(73)(74). The complexity of anuran bile salt profi les makes it diffi cult to summarize patterns of variation.…”
Section: Bile Salts Of Fi Shmentioning
confidence: 99%
“…Moreover, FICZ is conjugated metabolically with sulfate, and such conjugates have been detected in human urine (3), further verifying the presence of the parent compound in vivo. In addition to its efficient activation of AHR signaling, FICZ appears to be a potent activator of signaling involving the liver X receptor or pregnane X receptor pathways (35,36). On the basis of such findings, we propose that FICZ should be added to the list of bioactive signaling substances derived from Trp that now includes serotonin, melatonin, and the plant growth hormone indole-3-acetic acid.…”
mentioning
confidence: 96%